"Are you Swedish?" : the heterogeneous identity of Finland-Swedish students - Hildén, Linda (2024)
This study aims to shed light on how Finland-Swedish students perceive and understand their identity and the Swedish-speaking minority. According to the Finnish Constitution, the national languages of Finland are Finnish and Swedish. In Finland, there is a Swedish-speaking minority living mainly on the coast of the Baltic Sea. People who speak Swedish as their mother tongue are called Swedish-speaking Finns or Finland-Swedes. The present study is from the perspective of Finland-Swedish students who go outside the Swedishspeaking area to study in a predominately Finnish-speaking area of Finland. This aspect has hardly been researched to date. At the same time, this study is also a response to the call for more qualitative research on the Finland-Swedish minority. It is conducted through in-depth interviews and a focus group discussion, and the data is analysed using Bamberg’s three level model of narrative positioning. The research questions of the study are: How do Finland-Swedish students perceive their identity? How do FinlandSwedish students navigate their positioning in a predominantly Finnish-speaking environment? Interview data was collected from six participants, three of whom also participated in a focus group discussion. All participants self-identified as Swedish speaking Finns and the individual interviews were grouped into four categories: Finland-Swedish identity, Finland-Swedishness in Finnish-speaking areas, encounters, and Finland-Swedishness on a national level. The findings illustrate the heterogeneous identity of the Swedish-speaking Finns and the minority’s connection with bilingualism. Despite speaking Swedish, the participants felt strongly about their Finnish national identity. The study also shows how outsiders problematise the bilingual identity of Finland-Swedish students, which underlines the ‘one language-one ethnicity’ language ideology. However, the study reveals how the participants challenge the language ideology by telling people about their background to prove their Finnishness. The results show how the positioning in relation to other characters in ‘small stories’ bridges into the positioning in the social context. Furthermore, the study demonstrates that the legacy of the Swedish period is still present in contemporary Finland. In conclusion, there is a need for more interpersonal communication to improve the perception of Swedish-speaking Finns and the Swedish language in Finland.